Thermal Energy Storage in Dirt for Repowering Decommissioned Coal Plants - Alicia Wongel; Jacqueline A. Dowling; Lei Duan; Austin Vernon; Ian S. McKay; Ken Caldeira (Findings)
Thermal energy storage in dirt can have low energy-storage capacity costs, potentially allowing cost-effective repowering of decommissioned steam turbogenerators. Results from a stylized model indicate that thermal storage in dirt could play a substantial role in electricity systems reliant on wind, solar and natural gas, increasingly so with larger shares of wind and solar generation. When first entering a market, rapid discharge of large amounts of energy could present a key revenue opportunity under certain conditions. Over broad ranges of assumed technology costs, electricity generated from decommissioned turbogenerators repowered by thermal energy storage in dirt could cost-effectively help meet demand peaks currently met using fossil generators.